التمكين البيئي للمرأة الريفية في محافظة اللاذقية "دراسة تحليلية تقويمية لبرامج مشروع عين التينة" (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2018)
هدف البحث للتعرُّف على واقع التمكين البيئي التربوي للمرأة الريفية، كجزء من برنامج تمكين المرأة الريفية في مركز عين التينة في محافظة اللاذقية. وتحقيقاً لهدف البحث أعدت الباحثة استبيانة موجهة للنساء الريفيات تضمنت(29) سؤالاً للتعرف على التمكين البيئي للمرأة الريفية وكل مجال من مجالاته (التوعية، التدريب والتأهيل)، وتم التأكد من صدقها وثباتها. وبلغت عيّنة الدراسة (100) امرأة ريفية من النساء المستهدفات ببرامج تمكين المرأة الريفية. وقد أسفرت نتائج البحث عن وجود فرق جوهري ذي دلالة إحصائية بين متوسط العيّنة التي تمثلها مجموعة الأسئلة المتعلقة بمستوى التمكين البيئي، ومتوسط مفترض يمثل بالقيمة المتوسطة (2) التي تشير لمستوى متوسط أو مقبول بالنسبة لتمكين المرأة بيئياً. وأثبتت الدراسة وجود فرق جوهري بين متوسط العيّنة والمتوسط المفترض الذي يمثل مستوى متوسط للنشاطات التي يسعى المركز لتنفيذها في مجال التأهيل والتدريب لحفظ الموارد الطبيعية وصيانتها.  أظهرت الدراسة أيضاً وجود فرق جوهري بين متوسط العيّنة والمتوسط المفترض الذي يمثل مستوى متوسط للنشاطات التي يسعى المركز لتنفيذها في مجال التوعية والتأهيل والتدريب لإدارة الموارد الناضبة، وترشيد الاستهلاك، والتخفيف من الفقد. وبينت الدراسة أنه يوجد فرق جوهري بين متوسط العيّنة والمتوسط المفترض الذي يمثل مستوى متوسط للنشاطات التي يسعى المركز لتنفيذها في مجال التوعية والتأهيل والتدريب لمنع التلوث ومكافحته. توصلت الدراسة إلى وجود فرق جوهري بين متوسط العيّنة والمتوسط المفترض الذي يمثل مستوى متوسط للنشاطات التي يسعى المركز لتنفيذها في مجال التوعية والتأهيل والتدريب لمجال السلامة والصحة البيئية والجمال. إذاً على برامج تمكين المرأة الريفية أن تتخذ خططاً واستراتيجيات تسير عليها في تمكين المرأة الريفية بيئياً وتربوياً لكي تخفف من حدة المشكلات البيئية التي تتعرض لها المرأة، وبهدف الإسهام في صيانة البيئة ومنع حدوث مشكلات جديدة. This research aims at exploring environmental educational empowerment state of rural women, as a project part of rural women empowerment in al-Teeneh center at Latakia. In order to achieve this goal, the researcher prepared a questionnaire for rural women, it includes 29 questions to identify rural women environmental empowerment and every domain of its fields (education, training and rehabilitation). So, its internal consistency and validity were confirmed. The Study sample consists of 100 rural women targeted by rural women empowerment programs. Results showed significant differences between the sample average   represented by a set of questions concerning empowerment level, and an assumed enabling mean representing the average value that represents the medium or the acceptable level for women environmentally. Also, the study showed a significant difference between the average sample and the assumed average, which represents the average of activities level, pursued by the Centre, to be achieved in the field of rehabilitation and training domain of natural resources conservation and maintenance. However, this study showed a significant difference between the sample average and the assumed average, which represents the average of activities level , pursued by the Centre to be achieved in the field of rehabilitation and training domain of conservation of  non-renewable resources management and to mitigate losses. The study showed that there is a significant difference between the average sample and the average is assumed, which represents the average level of the activities pursued by the centre in the domain of education, rehabilitation and training for pollution prevention and control. So, the study, pointed out a significant difference between the sample mean and the assumed average, which represents the average level of the activities proposed to be implemented by the Centre in the domain of education, rehabilitation and training, on safety, environmental health and beauty. Therefore these programs for rural women enabling must take into consideration plans and strategies to be pursued in empowering rural women, environmentally and educationally, in order to harsen the environmental problems faced by women, and to contribute in environment maintenance and in preventing  new problems.